Challenges in the modelling of the pharmacokinetics and pharmacodynamics of an anti-cancer drug combination on urinary bladder cancer T24 cells: a technical review - Atshan, Suhad Hussein; Al-Humadi, Hussam W. (Pharmakeftiki, 2025)
The development of novel anticancer therapies requires rigorous preclinical evaluation in order to ensure both efficacy and safety prior to clinical translation. The T24 cell line, derived from human transitional bladder carcinoma, is a widely employed in vitro model owing to its aggressive phenotype and strong relevance to human disease pathology. It offers a valuable platform for investigating bladder cancer progression, drug responsiveness, and mechanisms of resistance. However, replicating the complex tumour microenvironment and accurately predicting in vivo therapeutic outcomes still pose significant challenges in vitro. The pharmacokinetics (PK) and pharmacodynamics (PD) of candidate agents must be carefully assessed, as these parameters often diverge markedly between in vitro and in vivo contexts. In vitro PK/PD modelling – linking drug concentration to biological effect – facilitates dose optimization, particularly when integrated with pulsatile drug administration and advanced methodologies that simulate the three-dimensional tumour microenvironment. Such approaches enhance the translational relevance of bladder cancer research and may improve therapeutic outcomes. This review underscores the critical importance of optimizing the experimental design of in vitro PK/PD models in an attempt to address prevailing limitations and advance bladder cancer therapy.